2023
DOI: 10.1039/d2cc06503g
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of atomic site catalysts for electrochemical CO2reduction

Abstract: The renewable-energy-powered electrochemical CO2 reduction (ECR) is a promising way capable of transforming CO2 to value-added products and achieving sustainable carbon recycling. By virtue of the extremely high exposure rate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 143 publications
0
20
0
Order By: Relevance
“…CO 2 reduction performance was measured in a flow cell with an alkaline electrolyte under constant-current testing conditions. We detected four gaseous products (H 2 , CO, CH 4 , and C 2 H 4 ) and four liquid-phase products (HCOO − , CH 3 OH, C 2 H 5 OH, and CH 3 COO − ) from direct CO 2 reduction based on the 13 CO 2 isotope labeling experiment (Figures S18−S20). Among them, HCOO − exhibits a significantly lower Faradaic efficiency (FE; <2%) than others.…”
Section: Experimental Evaluation Of Co 2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 reduction performance was measured in a flow cell with an alkaline electrolyte under constant-current testing conditions. We detected four gaseous products (H 2 , CO, CH 4 , and C 2 H 4 ) and four liquid-phase products (HCOO − , CH 3 OH, C 2 H 5 OH, and CH 3 COO − ) from direct CO 2 reduction based on the 13 CO 2 isotope labeling experiment (Figures S18−S20). Among them, HCOO − exhibits a significantly lower Faradaic efficiency (FE; <2%) than others.…”
Section: Experimental Evaluation Of Co 2 Reductionmentioning
confidence: 99%
“…15−23 Several prior studies suggested that heteroatom-doped carbon-supported isolated Cu atoms are not electrochemically stable under negative potentials of realistic CO 2 RR conditions and would likely be reduced to metallic Cu species, acting as the catalytic site for CO 2 reduction to CO, C 2 H 4 , and C 2 H 5 OH. 24−27 In situ reconstruction of single-atom Cu during CO 2 -to-CH 4 conversion was reported on oxide-supported isolated Cu, 13 Cu-based metal−organic frameworks, 28 and undoped carbon nanotube-supported Cu-phthalocyanine molecular catalysts. 29 However, to our knowledge, such dynamic reconstruction of single-atom Cu has not been demonstrated yet on N-doped carbon supports in CH 4 generation.…”
Section: Introductionmentioning
confidence: 99%
“…SiO 2 was used as a support to stabilize the Cu species, which formed abundant atomic Cu−O−Si interfacial sites. 120 The strong interaction between Cu and SiO 2 made the Cu−O−Si interfacial sites show ultrahigh reconstruction resistance (Figure 9g). And the atomic Cu−O−Si interface sites favored *CO protonation to further promote the CH 4 generation (Figure 9h).…”
Section: Ad Cu Catalysts For C 1 Productsmentioning
confidence: 99%
“…[11][12][13][14][15][16] Among these options, the electrochemical CO 2 reduction reaction (CO 2 RR) has emerged as one of the most promising routes to addressing the issues of recycling CO 2 and producing valuable chemical products. [17][18][19][20] Furthermore, the CO 2 RR can be driven by renewable (but intermittent) energy sources (such as wind, solar, and tidal) without extra CO 2 emission, and the reduction process can be easily performed by adjusting the potential range and current densities under ambient pressure and temperature. 17,21,22 However, the CO 2 RR suffers from two stable CQO double bonds (bond energy, 806 kJ mol À1 ) in the extremely inert linear CO 2 molecule, generally leading to a low energy efficiency with high overpotentials.…”
Section: Introductionmentioning
confidence: 99%